2004
DOI: 10.1002/jmv.20182
|View full text |Cite
|
Sign up to set email alerts
|

Role of beauty treatment in the spread of parenterally transmitted hepatitis viruses in Italy

Abstract: The aims of the study were to evaluate the role of beauty treatments in the spread of acute viral hepatitis B (HBV) and acute viral hepatitis C (HCV) in Italy. Data from the surveillance system for acute viral hepatitis (SEIEVA) during the period 1997-2002 were used. After exclusion of subjects <15 years or >55 years old and reporting intravenous drug use or blood transfusion, the association of acute HBV and HCV cases with beauty treatments (tattooing, piercing, manicure/chiropody, and barber shop shaving) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 20 publications
4
54
3
4
Order By: Relevance
“…31 Our result was similar to previous studies conducted in Vietnam that indicated that HBV genotype B was the most prevalent (63.0%-72.6%) followed by genotype C (18.0%-28.0%). [32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…31 Our result was similar to previous studies conducted in Vietnam that indicated that HBV genotype B was the most prevalent (63.0%-72.6%) followed by genotype C (18.0%-28.0%). [32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies reported that beauty treatment activities, especially shaving and tattooing, might be associated with HBV and HCV infections. [5][6][7][23][24][25] Our study demonstrated that the prevalence of HBV infection among beauticians in Quy Nhon City, Binh Dinh province was 7.3% (95% CI: 4.4-11.3). This result was similar to the reported global HBV prevalence, indicating that Viet Nam was classified as a region of high-intermediate level of HBV infection (5-8%).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A study conducted in Pakistan showed that women misjudge the approach for transmission , symptom and risks associated with disease though mass population was aware of the cause of disease 7 . Nazir reported that around 92% of subjects are aware of hepatitis B infection, only 16.4% of all the students have gone through the test of HBV infection and 37.5% students had taken the hepatitis B vaccine. Never thought of vaccination, lack of motivation, afraid of needles, lack of belief, and no need felt were the common reasons when they were inquired about not taking the hepatitis B vaccine 8 .…”
mentioning
confidence: 99%